2001
DOI: 10.1159/000045995
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Experimental Membranous Glomerulonephritis in Rats by an Anti-MHC Class II Antibody

Abstract: Background: We previously reported that idiopathic membranous nephropathy (IMN) strongly correlated with HLA-DRB1*1501-DRB5*0101-DQAI*0102-DQB1* 0602, a specific haplotype of human major histocompatibility complex (MHC), in Japanese patients. To investigate the role of MHC in the development of rat Heymann nephritis (HN), an animal model of membranous nephropathy, a monoclonal antibody (mAb) specific to rat MHC class II antigen (RT1B) was administered, and its effectiveness in inhibiting HN was assessed. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Thus, NTP-induced changes in inflammation might explain some of the "beneficial" effects of smoking. The Lewis rat has been used as an experimental animal model for many inflammatory and autoimmune diseases (10,21,40,41,46,47), and the transdermal NTP could be used to test the therapeutic potential of NT for various inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, NTP-induced changes in inflammation might explain some of the "beneficial" effects of smoking. The Lewis rat has been used as an experimental animal model for many inflammatory and autoimmune diseases (10,21,40,41,46,47), and the transdermal NTP could be used to test the therapeutic potential of NT for various inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…HN has a rapid and irreversible course and therefore it is not suitable for testing new treatment options. Previous work has shown that none of the pre‐ or post‐disease treatment protocols could significantly influence the three most important aspects of HN development that contribute to its establishment, namely pathogenic aab formation, progressive immune complex glomerulonephritis (ICGN) and proteinuria development 11–20 …”
mentioning
confidence: 99%
“…Treatment of this autoimmune kidney disease has been attempted by several means, but so far, no treatment options have held the promise of a cure Barabas et al 1970;Kupor et al 1976;Cattran 1988;Matsukawa et al 1992;Gilkeson et al 1996;Penny et al 1998;Yokoyama et al 1999;Hasegawa et al 2001). Indeed, researchers have tried various medications for this and other experimental animal autoimmune disorders.…”
mentioning
confidence: 99%
“…Indeed, researchers have tried various medications for this and other experimental animal autoimmune disorders. While certain treatments instituted before the occurrence of the disease have led to lessened morphological and functional changes Barabas et al 1970;Bagchus et al 1986;Nangaku et al 1996;Schiller et al 1998;Rieben et al 1999;Hasegawa et al 2001;Spicer et al 2001), treating animals in advanced disease stages has not altered eventual outcome. As solutions for treating autoimmune disorders in humans must come from animal experiments, there is considerable urgency to find specific treatments which might terminate such disease conditions.…”
mentioning
confidence: 99%